Methodological principles for teaching the reading of original texts using innovation (Journal of Pedagogical Inventions and Practices, 2023)
This study reveals the challenges of integrating systems in reading instruction to improve reading comprehension skills in students who have difficulty learning English as a second language. What is required of the teacher is quality education and experience. In this article we have reviewed the most important and useful information about developing reading comprehension in English language instruction. A pilot study was conducted to evaluate the effectiveness of systems and interventions to improve reading comprehension skills in context. The findings clearly show that there was a significant difference between the experimental groups. It can then be summarized that the systems and applications in general provide a motivating learning environment for reading instruction, which has a positive impact on improving students' reading skills.